Tracing the sources and formation pathways of atmospheric particulate nitrate over the Pacific Ocean using stable isotopes. (15th July 2019) - Kamezaki, Kazuki; Hattori, Shohei; Iwamoto, Yoko; Ishino, Sakiko; Furutani, Hiroshi; Miki, Yusuke; Uematsu, Mitsuo; Miura, Kazuhiko; Yoshida, Naohiro
Abstract: This paper presents isotopic compositions (δ 15 N and Δ 17 O values) of atmospheric particulate nitrate (p-NO3 − ) collected over the Pacific Ocean between 40°S and 68°N on two cruises using the Research Vessel Hakuho Maru . Six marine regions over the Pacific Ocean were categorized using backward trajectory analysis, and various ion concentrations were employed to assess the dominance of anthropogenic or non-anthropogenic sources. The δ 15 N(p-NO3 − ) values ranged from −15.4‰ to 2.5‰ over the Pacific Ocean between 40°S and 68°N. The range of the source δ 15 N(NOx ) values were calculated for each sample based on isotopic exchange/fractionation during oxidation from NOx (NO and NO2 ) to HNO3, and a range of −14.1 to 6.9‰ was yielded over the Pacific Ocean. Compared to other regions, extremely low δ 15 N(NOx ) values of −14.1‰ to −7.3‰ were found over the equatorial Pacific, and such values cannot be matched using conventional NOx apportionment. Emissions of specific oceanic nitrogen emissions of NH3 and alkyl nitrate are thus proposed for the equatorial Pacific. Results demonstrate the importance of the nitrogen recycling process between the ocean and lower atmosphere in the equatorial Pacific. Δ 17 O(p-NO3 − ) values and light flux were found to be generally well-correlated in most Pacific Ocean regions, and this result is consistent with the importance of photolysis for OH radical concentrations relative to the contribution of O3 in producing HNO3 from NOx . In contrast, Δ 17 O(p-NO3 − ) values for the eastern North Pacific region were higher than in other regions with similar light fluxes, which implies a contribution from halogens to p-NO3 − formation. Highlights: We present data sets of δ 15 N and Δ 17 O of atmospheric p-NO3 − over Pacific Ocean. The low δ 15 N in equatorial Pacific suggest N recycle between marine and atmosphere. The high Δ 17 O indicate NO3 − formation by halogen in the central North Pacific.